2010
DOI: 10.1080/00221301003645277
|View full text |Cite
|
Sign up to set email alerts
|

Does the Optimism Bias Affect Help-Seeking Intentions for Depressive Symptoms in Young People?

Abstract: Help-seeking is an adaptive means to address mental health difficulties, but sufferers often fail to seek assistance. This inaction may reflect optimism bias--that is, believing one is less susceptible to negative events than others. In the present study, the authors investigate optimism bias by presenting depressive symptoms in vignette form to 263 undergraduate participants. Participants were asked to imagine oneself or a peer-group friend suffering from presented symptoms and provide ratings of problem seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Females tend to be more likely to disclose to others their distress resulting from a mood disorder (Kalafat & Elias, 1992; Zimmerman, 1991) and access multiple forms of treatment more often than males (Milner & De Leo, 2010). As symptom severity increases, females have also reported more positive opinions of the benefits of getting help (Spendelow & Jose, 2010). The literature is limited regarding the types of adults Latino adolescents turn to in times of distress, especially involving SI.…”
Section: Sex and Race/ethnic Differences In Help Seekingmentioning
confidence: 99%
“…Females tend to be more likely to disclose to others their distress resulting from a mood disorder (Kalafat & Elias, 1992; Zimmerman, 1991) and access multiple forms of treatment more often than males (Milner & De Leo, 2010). As symptom severity increases, females have also reported more positive opinions of the benefits of getting help (Spendelow & Jose, 2010). The literature is limited regarding the types of adults Latino adolescents turn to in times of distress, especially involving SI.…”
Section: Sex and Race/ethnic Differences In Help Seekingmentioning
confidence: 99%
“…Fourth, this study examined only independent relationships between the identified variables, whereas researchers have outlined dynamic and bidirectional interactions between predisposing, enabling, and need factors associated with service use (14,15,69,77). This includes an interactive effect between sociodemographic variables and psychological distress in the prediction of service use (69).…”
Section: Limitationsmentioning
confidence: 99%
“…In terms of gender, women tend to be less optimistic than men across a number of research contexts, including depression (Hampson, Andrews, Lee, Foster, Glasgow, & Lichtenstein, 1998;Spendelow & Jose, 2010), unplanned pregnancy (Chapin, 1999), and cancer (Hampson et al, 1998). Others find no significant gender difference in optimistic bias (Fontaine & Smith, 1995;Weinstein, 1987).…”
Section: Optimistic Bias and Demographicsmentioning
confidence: 93%